Reducing the income tax burden for households with children: An assessment of the child tax credit reform in Austria - Michael Christl; Silvia De Poli; Janos Vargas (European Commission, Joint Research Centre (JRC), 2019)
This paper analyses the impact of the implementation of a child tax credit in Austria in 2019, not only on micro, but also on macro level by using a dynamic scoring methodology. First, we assess the fiscal and distributional impact of this reform using the microsimulation model EUROMOD. Second, we estimate labour supply impacts of the reform based on a structural discrete choice framework. Third, we evaluate the macroeconomic impacts of the reform, by calibrating and shocking QUEST, the DSGE model of the European Commission, with the micro-based results for the implicit tax rate, the non-participation and the labour supply elasticities. We show that the child tax credit reform in Austria reduces inequality, lowers the poverty rate in general, but by definition only for households with children. Overall the reform has a positive impact on labour supply, both on the extensive and on the intensive margin, especially for women. On the macro-level (and in the long-run), our model suggests a positive impact on employment. Additionally, we find that parts of the tax decrease can be potentially captured by the employer, meaning that gross wages would fall slightly. However, we find small but positive effects on GDP, investment and consumption, although the longrun macroeconomic effects depend crucially on how the government compensates the missing tax revenues after the reform. Accounting for these effects at the micro level, we show that the second round effects are important to take into account, because they provide insights into the medium-term distributional impact of the reform.
Keywords: H24; H31; I38; 330; EUROMOD; tax credit; reform; DSGE; labour supply; microsimulation; discrete choice